This shows that both functions have the same y-intercept
<h3>Polynomial and exponential functions</h3>
Given the following functions as shown:
f(x) = -x^2 + 2x + 1
g(x) = 2^x
The y-intercept occurs at x = 0
For f(x) = -x^2 + 2x + 1
f(0) = -0^2 + 2(0) + 1
f(0) = 1
For the g(x), the y intercept is caculated as:
g(0) = 2^0
g(0) = 1
This shows that both functions have the same y-intercept
Learn more on intercept here: brainly.com/question/1884491
Answer:
False
Step-by-step explanation:
Answer:
19
Step-by-step explanation:
The n th term of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = 3 and d = 4 , thus
a₅ = 3 + (4 × 4) = 3 + 16 = 19
Answer:
0.11627907
Step-by-step explanation: